First CCD UBVI photometric analysis of four moderately young open clusters in the third galactic quadrant - Piatti, Andres Eduardo (2010)
We present CCD photometry in the Johnson UBV and Kron-Cousins I systems down to V~ 22.0 for the open clusters NGC 2311, Trumpler 6, NGC 2432 and BH 54 and their surrounding fields. Trumpler 6 and BH 54 have never been studied before and so we provide, for the first time, estimates of their fundamental parameters. We obtained colour-magnitude diagrams (CMDs) and colour-colour diagrams cleaned from field star contamination by statistically subtracting stars in terms of spatial density, magnitude and colour distributions. Cluster angular radii were estimated from star counts in appropriate-sized boxes distributed throughout the entire observed fields. Using the cleaned CMDs and colour-colour diagrams, we applied sound photometric membership criteria to discriminate cluster members from interloper field stars. The interstellar extinction across the cluster fields derived from the 100-μm dust emission full-sky maps can be considered uniform within the quoted uncertainties. The E(B-V) and E(V-I) colour excesses and the apparent distance moduli of the clusters were estimated from the fit of the zero-age main-sequence to the colour-colour diagrams and CMDs, respectively. Cluster ages were determined from the comparison of the four clusters' CMDs with solar metallicity theoretical isochrones of the Geneva group. All the clusters were found to be moderately young objects, their ages ranging between 60 and 250 Myr. © 2010 The Authors. Journal compilation © 2010 RAS.